PHRASEOLOGISMS IN LITERATURE: ENHANCING MEANING AND STYLE - Boltaeva Mekhrangiz Khaydarovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Phraseologisms are an essential feature of literary language, adding depth, expressiveness, and stylistic nuance to texts. This study examines the role of phraseological expressions in literature, highlighting how they enrich meaning, develop characters, and create cultural and emotional resonance. By analyzing examples from classical and contemporary English literature, the research demonstrates that phraseologisms enhance stylistic sophistication, contribute to narrative voice, and facilitate readers’ understanding of complex ideas. Understanding phraseologisms in literary contexts is vital for both literary analysis and advanced language learning.